2020
DOI: 10.3233/xst-190628
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation of skeletal and dental changes in patients with skeletal class III malocclusion and facial asymmetry after surgical-orthodontic treatment

Abstract: OBJECTIVE: To evaluate skeletal and dental changes in patients with skeletal Class III malocclusion and facial asymmetry after surgical-orthodontic treatment using cone-beam computerized tomography (CBCT). METHODS: This study included forty adult patients diagnosed with skeletal Class III malocclusion and asymmetry who underwent either isolated mandibular surgery or bimaxillary surgery. CBCT scans were taken before treatment (T0), at the completion of presurgical orthodontic treatment (T1) and after treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Supplementary Table 3 summarizes the NOS results. Most of the studies were assessed as moderate quality, 12 - 48 while a few were assessed as high quality. 14 , 49 - 62 The studies were classified as high quality when the comparability of cohorts was appropriately addressed based on the study design or analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Table 3 summarizes the NOS results. Most of the studies were assessed as moderate quality, 12 - 48 while a few were assessed as high quality. 14 , 49 - 62 The studies were classified as high quality when the comparability of cohorts was appropriately addressed based on the study design or analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Ming et al [ 30 ] reported that they did not find a significant difference between the angulations of the lower and upper first molars before treatment, before orthognathic surgery, and after treatment in patients with skeletal class 3 and facial asymmetry. Similarly, in our study, while there was no significant change in the angulations of the lower and upper first molars in skeletal class 3, between the before and after treatment, mostly significant angulation changes were found in skeletal classes 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with two-dimensional latero-lateral tele radiography, 3D cephalometric cone beam CT has advantages such as more precise measurement point positioning and clearer relationship analysis between bones and surrounding tissues. Therefore, the latter method is often used to evaluate the effects of oral and maxillofacial treatments such as orthodontic treatment 32,33 . By describing the changes in the palate after TSDO in all dimensions in detail, we suggest anticipation of the changes in the palate after surgery, which should be an important part of the preoperative evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The Journal of Craniofacial Surgery Volume 33, Number 2, March/April 2022 Influence of Bone-Borne Trans-Sutural orthodontic treatment. 32,33 By describing the changes in the palate after TSDO in all dimensions in detail, we suggest anticipation of the changes in the palate after surgery, which should be an important part of the preoperative evaluation. However, this study has some limitations.…”
Section: Discussionmentioning
confidence: 99%